Effectiveness Of Lemon Aromatherapy In Reduce Nausea And Vomiting In First Trimester Pregnant Women - Girsang, Rut Yohana (Akademi Kebidanan Bunga Husada Samarinda, 2023)
Pregnancy usually accompanied by discomfort often experienced pregnant mother especially on first trimester pregnancy is nausea and vomiting. One therapy safety and can be give to pregnant women who experienced nauseous vomit by giving lemon aromatherapy. The aim of this research is to know the effectiveness of lemon aromatherapy in reducing nauseous vomit to pregnant women First trimester at the Poli Kebidanan Rumah Sakit Umum Panyabungan Tahun 2021. This research using research design Quasi Experiment in one group (one group pretest posttest). Sampling technique using total sampling by number of samples 16 pregnant women and data collection done using observation sheet. The Research result shows that most of the frequency of nausea and vomiting before intervention is weight (50%) and mostly frequency of nausea and vomiting after intervention is mild (75%), p value equal to 0.003 (p less than 0.05). Based on statistical results can be concluded that there is effectiveness lemon aromatherapy in reducing nauseous vomit to pregnant women First trimester at the Poli Kebidanan RSUD Depok Tahun 2022. The Recommended to pregnant women who experienced nauseous vomit consuming lemon aromatherapy to lower frequency of nausea and vomiting.